The heart of winter : a book about helping people ([Hong Kong] : Time Life Asia, 1997)
"One dark night a stranger knocks at the door of a kind hearted old lady and asks her to help save his sick child. The old lady sets out into the snowy night without thinking of herself or her own hardship. Later, when the child is cured, the old lady finds that helping others can bring its own rewards."--Cover.
Keywords: Values -- Juvenile literature; Kindness -- Juvenile literature